Historical Anthology of Music by Women - Briscoe, James R. (Indiana University Press, 1986)
This collection of 51 works by 37 composers is the first compendium of its kind. The compositions, spanning eleven centuries of Western art music, are vital and important and illustrate advanced compositional trends of their age. The earliest works reproduced are two Byzantine chants by Kassia (fl. 840); the most recent is the first movement of Ellen Zwilich's Symphony No. 1, which received the Pulitzer Prize for music in 1983. Some of the outstanding early composers included are Hildegard von Bingen (fl. 1150), Maddalena Casulana (fl. 1560), Francesca Caccini (fl. 1620), and Elisabeth-Claude Jacquet de la Guerre (fl. 1700). From the eighteenth and nineteenth centuries come compositions by Marianne von Martinez, Maria Szymanowska, Fanny Mendelssohn Hensel, Pauline Viardot, Clara Schumann, and Amy Beach. Among the twentieth-century composers are Ruth Crawford Seeger, Grazyna Bacewicz, Louise Talma, Pauline Oliveros, and Thea Musgrave. Each composer is introduced in a short essay written by an authority on the period or, in the case of some of the living composers, the artist herself. The essays discuss the main aspects of the individual composer's life, her style, and her output, and they suggest additional readings. Since this anthology is designed for use in courses in women's studies, music appreciation, and music history, all style periods and important genres are represented, and all the works in the collection are available on recordings or are easily performed. Historical Anthology of Music by Women reflects the growing interest in and recognition of women's contributions to the arts in general and to music in particular.